Avaliação das atividades anti-inflamatórias e antioxidantes da gliclazida em modelo experimental de mucosite oral induzida por 5-fluorouracil - Mafra, Cristiane Assunção da Costa Cunha (2019)
Oral mucositis (OM) is acute inflammation of the oral mucosa, the most important sequelae from radiotherapy and/or chemotherapy treatments. The lesions in the oral cavity are severe and painful, and can lead to sepsis and death. There is no single protocol for preventing or curing OM. From the perspective of finding pharmacological therapies to prevent OM, we propose an investigation of the pleiotropic effect of commercial drugs, among them gliclazide, an anti-diabetic with anti-inflammatory and anti-oxidant side action which has never studied regarding OM. This study aimed to evaluate the effect of gliclazide on an experimental OM model induced by 5-fluorouracil. Male hamsters were pretreated with oral gliclazide (1, 5 or 10 mg/kg) for 10 days. The mucosal samples of the animals were submitted to histopathological and immunohistochemical analysis (COX2, iNOS, MMP-2, NFκB P65, GPx) and immunofluorescence (P-selectin). Levels of IL-1β and TNF-α, myeloperoxidase activity (MPO) and malondialdehyde levels (MDA) were investigated by ultraviolet-visible spectroscopic analysis. Protein expression of NFkB NLS P50 was analyzed by western blotting. The group treated with gliclazide at a dose of 10 mg/kg presented erythema, absence of erosion and mucosal ulceration with a score of 1 (1-2) (p <0.01) in the clinical findings. The histopathological data of the gliclazide 10 mg/kg group showed reepithelialization, a discrete mononuclear inflammatory infiltrate, and ulcers with a score of 1 (1-1) (p <0.01). Treatment with 10 mg/kg gliclazide reduced the activity levels of MPO (p <0.001), MDA (p <0.001) and NFκB NLS P50 (p <0.05), resulting in low immunostaining for Cox-2, iNOS (p <0.05), NFκB P65 (p <0.05) and negative immunoreaction for MMP-2. For Gpx, staining was restored in the GLI 10-FUT group compared to 5FUT/saline (p <0.05). Immunofluorescence showed a decrease in P-selectin levels (p <0.001) after treatment with 10 mg/kg gliclazide (p <0.05). Furthermore, 10 mg/kg gliclazide attenuated OM severity and reduced oxidative stress, and 5-FU induced OM in hamsters.